CEP164-null cells generated by genome editing show a ciliation defect with intact DNA repair capacity - Daly, Owen M.; Gaboriau, David; Karakaya, Kadin; King, Sinéad; Dantas, Tiago J.; Lalor, Pierce; Dockery, Peter; Krämer, Alwin; Morrison, Ciaran G. (Journal of cell science, 2016)
Skip to Next Section - Primary cilia are microtubule structures that extend from the distal end of the mature, mother centriole. CEP164 is a component of the distal appendages carried by the mother centriole that is required for primary cilium formation. Recent data have implicated CEP164 as a ciliopathy gene and suggest that CEP164 plays some roles in the DNA damage response (DDR). We used reverse genetics to test the role of CEP164 in the DDR. We found that conditional depletion of CEP164 in chicken DT40 cells using an auxin-inducible degron led to no increase in sensitivity to DNA damage induced by ionising or ultraviolet irradiation. Disruption of CEP164 in human retinal pigmented epithelial cells blocked primary cilium formation but did not affect cellular proliferation or cellular responses to ionising or ultraviolet irradiation. Furthermore, we observed no localisation of CEP164 to the nucleus using immunofluorescence microscopy and analysis of multiple tagged forms of CEP164. Our data suggest that CEP164 is not required in the DDR.
Gesehen am 06.05.2020